1973
DOI: 10.1021/jo00965a018
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular propagation in the oxidation of n-alkanes. Autoxidation of n-pentane and n-octane

Abstract: l-Acetyl-l-methylcyclohexane: bp 68-70°(7 mm) [lit.26 bp 80-8.5°(16 mm)]; 13.8 g (66% based upon 150 mmol of olefin) isolated; ir 1700 cm-1; nmr r 8.0 and 9.0 [sharp s, H3CCOCCH8]; vpc (130°a nd 150°) 18 showed a single compound. The 2,4-DNP had a melting point of 131-132°( lit.26 mp 132°) and the semicarbazone melted at 183-185°(lit.26 mp 186-187°).3,3-Dimethyl[3.2.1]bicyclooctanone-2 (7): bp 30-40°(0.3 mm); ir 1710, 3050, and 1610 cm-1 (the latter indicated olefinic contamination); vpc (200°)18 indicated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…This loss is expressed by translational and rotational entropy contributions according to the following expression [58]: elementary reactions rarely involve reactive pathways comprising intramolecular reactions. We evaluate accuracy limits implicit in our calculated kinetic data based on a comparison with corresponding experimental values obtained by Van Sickle and co-workers [52,59], for the intramolecular 1,5-hydrogen shift during auto-oxidation of liquid 2-peroxypentane. Our kinetic estimation for this reaction affords a barrier of 81.9 kJ/mol and log A of 13.1 s −1 ; i.e., in agreement with the corresponding experimental assessment for this reaction, 82.4 kJ/mol and 11.5 s −1 , respectively.…”
Section: Kinetic Considerationsmentioning
confidence: 99%
“…This loss is expressed by translational and rotational entropy contributions according to the following expression [58]: elementary reactions rarely involve reactive pathways comprising intramolecular reactions. We evaluate accuracy limits implicit in our calculated kinetic data based on a comparison with corresponding experimental values obtained by Van Sickle and co-workers [52,59], for the intramolecular 1,5-hydrogen shift during auto-oxidation of liquid 2-peroxypentane. Our kinetic estimation for this reaction affords a barrier of 81.9 kJ/mol and log A of 13.1 s −1 ; i.e., in agreement with the corresponding experimental assessment for this reaction, 82.4 kJ/mol and 11.5 s −1 , respectively.…”
Section: Kinetic Considerationsmentioning
confidence: 99%
“…We consider the oxidation of an alkane that propagates through intermolecular reactions rather than through intramolecular [65][66][67] onesi.e. we assume that the considered alkane does not have the structural component H-CR 1 -CH2-CR 2 -H, where R 1 and R 2 are alkyl groups (this is valid for heptane and isooctane).…”
Section: Degradation Of the Fuel Filmmentioning
confidence: 99%
“…2) The radicals propagate the chain by intermolecular (reaction (3)) or, in certain circumstances, by intramolecular (reaction (4)) reactions 21), 22) , for example:…”
Section: Self-reactions Of Peroxyl Radicalsmentioning
confidence: 99%
“…It should be noted that the ester radicals are not simply produced by reactions between the ester substrate and alkoxyl radicals (reactions (21) and (23)). The latter radicals also fragment (reactions (20) and (22)) and to different extents as shown by the formation of methane. This was determined quantitatively and showed that almost all of the methyl radicals can be accounted for as methane and thus abstraction from the parent ester is their most important reaction.…”
Section: Preferred Site Of Attack By Oxygenated Radicals On Neopentylmentioning
confidence: 99%